Critique, Rediscovery and Revival in Development Studies. Issue 4 (July 2015) - Arsel, Murat; Dasgupta, Anirban; Arsel, Murat
ABSTRACT This article acts as the Introduction to the Debate that follows. It contends that the so‐called impasse in development has been a constant feature of the field and is an indicator of its self‐critical outlook rather than any deep‐seated existential crisis. It unpacks the various dimensions of ongoing debate regarding the future of development studies, probing its policy relevance and legitimacy, interdisciplinarity, geographic focus and relationship with post‐structuralist and Marxist thought. In order to revive and reorient the field in line with the contemporary world, the article proposes to return to an explicit Marxist/Marxian political economy framework to analyse the dynamics of capitalism in its local, national and global dimensions. Such a move would entail turning away from the increasingly dominant approach of critique for the sake of critique. Instead, the article argues that development studies can only fulfil its mission if scholars keep the goal of emancipatory development and change in mind when they engage with contemporary capitalist processes.